Challenges in Social Network Research : Methods and Applications - Ragozini, Giancarlo; Vitale, Maria Prosperina (Cham : Springer International Publishing : Imprint: Springer, 2020)
The book includes both invited and contributed chapters dealing with advanced methods and theoretical development for the analysis of social networks and applications in numerous disciplines. Some authors explore new trends related to network measures, multilevel networks and clustering on networks, while other contributions deepen the relationship among statistical methods for data mining and social network analysis. Along with the new methodological developments, the book offers interesting applications to a wide set of fields, ranging from the organizational and economic studies, collaboration and innovation, to the less usual field of poetry. In addition, the case studies are related to local context, showing how the substantive reasoning is fundamental in social network analysis. The list of authors includes both top scholars in the field of social networks and promising young researchers. All chapters passed a double blind review process followed by the guest editors. This edited volume will appeal to students, researchers and professionals.
Introduction. - Synchronization costs in dynamics of multilevel networks -- Socio-cultural Cognitive Mapping to Identify Communities and Latent Networks -- Bootstrapping the Gini Index of the Network Degree: An Application for Italian Corporate Governance -- Association rule and network analysis for exploring comorbidity patterns in health system -- A mixture model approach for clustering bipartite networks -- Big data and Social Network Analysis: foundations, perspectives and applications in Economic History -- Networks and Context: Algorithmic Challenges for Context-Aware Social Network Research -- Unraveling Innovation Networks in Conservation Agriculture using Social Network Analysis -- Mapping the informal organization through the urban activism: the case of self-organized spaces in the city of Naples -- The paths of the Italian young poets. A Social Network Analysis of the contemporary poetic field -- A data-driven method to forma DEA-based network -- Multilayer network analysis of innovation intermediaries' activities -- Inter-Organizational Networks and Third Sector: Emerging Features from two Case-Studies in Southern Italy.
Keywords: Data mining; Sociology -- Methodology; Artificial intelligence; Database management; Graph theory; Data Mining and Knowledge Discovery; Sociological Methods; Artificial Intelligence; Database Management; Graph Theory; Electronic books